Synthesis and characterization of bubble wrap-like hollow barium silicate–carbonate nanospheres for the epoxidation of styrene - Tan, Kok Hou; Iqbal, Anwar; Adam, Farook; Abu Bakar, N.H.H.; M. Yusop, Rahimi; Ahmad, Mohammad Norazmi (Elsevier, 2020)
Novel porous bubble wrap-like hollow barium silicate–carbonate nanospheres were successfully prepared at a barium/CTAB molar ratio of 0.75 and 1.00. The average pore size, BET surface area and total pore volume of the most catalytically active catalyst in the epoxidation of styrene, 1.00BaMST were 5.0 nm, 42 m2 g−1 and 0.0771 cm3 g−1, respectively. The styrene epoxidation reaction was carried out using H2O2 as an oxidant. Barium silicate and carbonate groups detected on the catalyst’s surface are proposed to activate the H2O2 and selectively oxidize the styrene to styrene oxide. The 1.00BaMST achieved 63.3% of styrene conversion and 77.8% of epoxide selectivity at mild conditions (3 h, 60 ◦C). The reaction energy barrier was calculated to be 17.3 kJ mol−1.